About šekam and šotor: The Development of the Initial Vs/šC- in Middle and New Persian - Aliyari Babolghani, Salman (Journal of Iranian Linguistics, 2024)
The purpose of this paper is to survey the phonological evolution of the initial sequence Vs/šC- in Persian as reflected, for instance, in Middle Persian iškamb > New Persian šekam ‘belly’, and to explore philological issues associated with this evolution.